Impact Quality Product, Distribution Channels and Personal Selling Toward Polythene Tail Costumer Loyalty in PT. United Rope: Impact Quality Product, Distribution Channels and Personal Selling Toward Polythene Tail Costumer Loyalty in PT. United Rope - Purnama Yanti Purba; Ravika Elda Siregar; Alvin Alvin; Alimin Fendi (Institute of Computer Science (IOCS), 2020)
This research was conducted at PT. United Rope. The porpuse of this study was to test and analyze the influence of Product Quality, Distribution Channels and Personal Selling on polythene Rope Customer Loyalty at PT.United Rope. There is a decrease in customer loyalty caused by customer loyalty. The approach of this reseach is based on a quantitive approach. The population in this study amounted to 217 customers. The sampling technique used was simple random sampling. The number of samples in this study were 144 customers. The results of calculation of hypothesis testing partially Product Quality has a positive and significant effect on Polythene Rope Customer Loyalty at PT. United Rope. Partially Distribution Channels have a positive and significant effect on Polythene Rope customer loyalty at PT, United Rope. Partially Personal Selling has a positive and significant effect on Polythene Rope Customer Loyalty at PT. United Rope. Simultaneously Product Quality, Distribution Channels and Personal Selling have a positive and significant effect on Polythene Rope Costumer Loyalty at PT. United Rope. The coefficient of determination test result obtained am adjusted R Square value of 0.42, in dependent variable, namely customer loyalty, can be expalined by the variation of the idependent variabels, while the remaining 58% is explained by other variables not examined in this study, such as quality, brand awareness, service and others